Performance of an Effective SAR Polarimetric Calibration Method Using Polarimetric Active Radar Calibrators: Numerical Simulations and LT-1 Experiments - Yibin Chen; Liang Li; Guikun Liu; Zhengshuai Li (Remote Sensing)
This paper presents a new approach to polarimetric calibration, extending classical PARC-based methods by exploring new matrix combinations that broaden the applicability of the existing techniques. By investigating alternative matrix configurations, the proposed method not only enhances the flexibility of conventional calibration approaches but also identifies matrix combinations that offer superior performance advantages. The influence of the SNR and scattering matrix error of PARC on the proposed method is evaluated by numerical simulations. The results demonstrate that the proposed method is highly accurate for PARCs with an SNR greater than 34 dB and with single-channel scattering matrix deviations less than −40 dB and four-channel scattering matrix deviations less than 0.5 dB. The effectiveness and precision of the method were validated through calibration experiments conducted on the L-band polarimetric synthetic-aperture radar aboard the LT-1 satellite. The experimental results demonstrate that the amplitude and phase estimation errors of channel unbalance are less than 0.6 dB and 4.5°, respectively, and that the crosstalk estimation error is less than −33 dB. Furthermore, the effectiveness of the method is validated through trihedral corner reflector correlation experiments and the synthesis of pseudo-color images via Pauli decomposition. The theoretical polarization characteristics of the reference target exhibited a high degree of agreement with the calibrated polarization characteristics.